Policy Change Explanation by Advocacy Coalition Framework Case Study: Iran Petroleum Contract (IPC) - Mohammad Sadiq Torabzadeh Jahromi; Seyyed Kazem Hoseini; Mohammad Noruzi (بهبود مدیریت, 2017)
The analysis of public policy change and stability is one of the most attractive and yet challengeable subjects in policy research and use of policy process theories is very useful and helpful for explanation of this change. On the other hand, given to being contractual frameworks (especially in upstream section of petroleum industry) as important policies in this field, it is important and critical to understand their formation process and can prepare the context of their pathology, correction and development. In this article, the process of formulation and emergence of Iran Petroleum Contract (IPC) to its ratification is studied and explained by Advocacy Coalition Framework (ACF) as analysis Framework. Essence and goals of research have demanded to convey this article with qualitative case study. Document study, direct observation and analysis of visual and audio archives have used for data gathering. Focus group and expert opinion have served for validation of outputs and scrutinization in data analyzing. Research results show the strength of advocacy coalition framework in this process explanation, and could explain three stages in IPC formation: 1. Coalitions emergence. 2. Policy blockage. 3. Deadlock breaking and ratification of new policy.